Creative Technology / A Classroom Resource - Aitken John; Holmes Mcdougall; Mills George (1987)
Introduction, Case History, Canyon Problem, Teaching Notes, Part One: Problems, Individual Problem Notes, Problems 1-100, Part Two: Ideas and Sketches and Solutions, Appendices, Wanted Poster, Science and Technology Certificate, Research and Development Log, Topic Index to Part Two.